2021
DOI: 10.1007/s40261-021-01080-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Body Mass Index on the Efficacy of Biological Therapies in Patients with Psoriasis: A Real-World Study

Abstract: Background The efficacy of biological therapies used for the treatment of chronic plaque psoriasis can be influenced by numerous variables including body mass index (BMI). Objective This study aimed to evaluate the impact of BMI on the short-term and long-term efficacy of biological therapies in clinical practice and to identify the best therapeutic options in obese patients (BMI ≥ 30 kg/m 2 ). Methods A multicentric retrospective study was conducted in patients who initiated a biological therapy during the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 53 publications
1
33
1
Order By: Relevance
“…[16][17][18] High weight does not seem to compromise the response to brodalumab, 19 the role of the weight in the response to ixekizumab shows contradictory results in the current literature. 18,20 In our study obesity proved to be a negative predictor of response to risankizumab in some of the outcomes analyzed: in the achievement of PASI 100 at week 28, reached by 22% of obese patients versus 58% of non-obese patients (p = 0.007), and in the mean PASI at 28 weeks 1.7 vs. 0.9 (p = 0.006). Other significant differences were seen in the attainment of PASI 100 at week 40 and PASI <3 at week 40.…”
Section: Discussionmentioning
confidence: 57%
“…[16][17][18] High weight does not seem to compromise the response to brodalumab, 19 the role of the weight in the response to ixekizumab shows contradictory results in the current literature. 18,20 In our study obesity proved to be a negative predictor of response to risankizumab in some of the outcomes analyzed: in the achievement of PASI 100 at week 28, reached by 22% of obese patients versus 58% of non-obese patients (p = 0.007), and in the mean PASI at 28 weeks 1.7 vs. 0.9 (p = 0.006). Other significant differences were seen in the attainment of PASI 100 at week 40 and PASI <3 at week 40.…”
Section: Discussionmentioning
confidence: 57%
“…The IL-17A inhibitor secukinumab demonstrated an inverse association of LDA and BMI in PsA after 6 months of treatment, perhaps due to greater serum IL-17 levels in patients with BMI ≥25 versus <25 kg/m 2 43. However, in PsO, a real-world study of secukinumab and the IL-17 inhibitor ixekizumab showed lower rates of skin response at 12 and 24 weeks and at 24 weeks, respectively, among patients with BMI ≥30 versus <30 kg/m 2 44. In the current post-hoc study, guselkumab Q4W and Q8W effect at week 24 was maintained through week 52 regardless of sex and obese versus non-obese status, supporting the potential benefits of guselkumab in treating these patient subgroups.…”
Section: Discussionmentioning
confidence: 98%
“…Their 7-year retrospective study showed that, compared to infliximab (where mean BMI increased from 24.7 to 25.7 kg/m 2 after 7 months), treatment with secukinumab maintained mean BMI levels to a constant value of 25.2. Based on their findings, it is therefore suggested that secukinumab exerts a neutral effect on body weight and could therefore constitute a more advantageous alternative for obese patients undergoing TNFI therapy [35]. In the same manner, results from a 12-week phase 3 clinical trial (UNCOVER-1, UNCOVER-2, and UNCOVER-3) measuring for cardiovascular and other parameters showed that ixekizumab had a neutral effect on both cardiovascular-related variables and body mass, as no weight gain was observed in patients receiving ixekizumab therapy at 12-week follow-up treatment [36].…”
Section: Il-17a Inhibitors and Bmimentioning
confidence: 99%